2017
DOI: 10.5433/1679-0359.2017v38n3p1133
|View full text |Cite
|
Sign up to set email alerts
|

Does competition between soybeans and Wild Poinsettia with low-level resistance or susceptibility to glyphosate affect physiology and secondary metabolism?

Abstract: The Wild Poinsettia (Euphorbia heterophylla L.) has elevated potential to reduce the soybean yield and is a difficult to control plant due to herbicide resistance. The objectives of this study were to determine the changes in the photosynthetic physiological parameters, secondary metabolite levels, cellular damage, and antioxidant system activity in soybean plants and Wild Poinsettia biotypes with a low level of resistance or susceptibility to glyphosate in competition with soybeans. Two replacement series exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In soybean and bean, Piasecki et al [ 13 , 14 ] showed that H 2 O 2 levels, APX, and CAT activity decreased with the increase in volunteer corn density, while SOD activity increased commensurate with weed density. Another study documented that the interference of wild poinsettia ( Euphorbia heterophylla ) on soybean did not result in any cellular damage or change in SOD, CAT, and APX enzyme activity in soybean [ 34 ]. Darmanti et al [ 10 ] studied soybean under purple nutsedge ( Cyperus rotundus L.) competition and found reduced activities of SOD, CAT, and APX in soybean.…”
Section: Modulation Of Enzymes and Antioxidant Genes Induced By Wementioning
confidence: 99%
“…In soybean and bean, Piasecki et al [ 13 , 14 ] showed that H 2 O 2 levels, APX, and CAT activity decreased with the increase in volunteer corn density, while SOD activity increased commensurate with weed density. Another study documented that the interference of wild poinsettia ( Euphorbia heterophylla ) on soybean did not result in any cellular damage or change in SOD, CAT, and APX enzyme activity in soybean [ 34 ]. Darmanti et al [ 10 ] studied soybean under purple nutsedge ( Cyperus rotundus L.) competition and found reduced activities of SOD, CAT, and APX in soybean.…”
Section: Modulation Of Enzymes and Antioxidant Genes Induced By Wementioning
confidence: 99%
“…With the exception of the cultivar DM 66i68 which showed a reduction in LA with an increase in competitor density, possibly due to a genetic differentiation that exists between the cultivars. ULGUIM et al (2017) reported that one of the determining factors for greater competitive capacity is the increase in light interception for chemical energy production by the photosynthetic process. Thus, RP and TRP related to LA prove to be important characteristics in soybean cultivars with greater competitive capacity, when associated with I. indivisa.…”
Section: Resultsmentioning
confidence: 99%